Being “resilient” and achieving “resilience”: From governmental discourses to the national research agenda in the contexts of food insecurity and cost of living - Sara Vilar-Lluch; Donna Clutterbuck; Michael Kranert; Dianna Smith; Sarah Nield; Nisreen A. Alwan (PLoS ONE, 2025)
The concept of ‘resilience’ is pervasive, permeating academic disciplines and political discourses. This paper considers (i) the construal of ‘resilience’ in the contexts of food insecurity and cost-of-living in governmental discourses in the United Kingdom (UK); (ii) to what extent the political representations are reflected in research funding calls of UK national funding bodies, thus showing possibility of shaping research agendas; and (iii) to what extent official uses of ‘resilience’ reflect lay understandings. We are combining a corpus-based discourse analysis of UK governmental discourses and research funding calls with a study of focus group discussions. Representations of ‘resilience’ are further compared with those available in general English corpora. We are observing a shift in the use of ‘resilience’: from an individual psychological attribute to a primarily socioeconomic and environmental characteristic. Funding calls construe resilience in relation to communities, reflecting economy and environment adaptability, whereas governmental discourses frame references to individuals in terms of ‘vulnerability’. Focus groups reveal divergent conceptions of ‘resilience’, which may lead to potential misunderstandings. While this variety of uses may be productive in political discourses for rhetorical purposes, there is a need for specificity in shaping research and in public-facing communications.